Analisis Kebijakan Pendidikan: Studi Peran Kepemimpinan Pendidikan Dalam Penguatan Investasi Dan Pendidikan Seni Budaya - Gunada, I Wayan Agus (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2024)
The purpose of writing this article is a study of education policy. The role of educational leadership is very central in strengthening educational investment, especially in arts and culture education. 'Curriculum Merdeka' as a new policy at the higher education level in Indonesia, provides the widest possible opportunity for students to study on and off campus. One of the programs is entrepreneurship for students to express according to their interests. The study was conducted with a literature review study approach. Based on the results of the analysis, it was found that leadership activities greatly support the process of art and culture education, leadership is carried out not only as a position, but as a manager and supervisor. Educational investment in the arts and culture strengthens the understanding of art education is not only a process, but a capital developed for the achievement of success in the future. Entrepreneurship for students really needs to be improved, so that it becomes an option in achieving success when completing education. So that the role of educational leadership is very central in supporting the 'independent curriculum' policy in Indonesia. It is hoped that the writing of this study can be useful to add insight, and can be a reference library for relevant research in the future.